The Role of Repeated Exposure and Message Fatigue in Influencing Willingness to Help Polar Bears and Support Climate Change Mitigation. Issue 4 (August 2022) - Lu, Hang
Repeated exposure and its associated fatigue are key obstacles to engagement that remain insufficiently addressed for climate change communication. To explore this issue, this study randomly assigned U.S. adults ( N = 933) to one of five experimental conditions (number of polar bear news headlines: 0 vs. 1 vs. 3 vs. 7 vs. 10), in which they were exposed to a total of 20 news headlines in a brief amount of time. Overall, this study did not find evidence supporting the inverted-U shaped model concerning repeated exposure. In addition, chronic message fatigue played a moderating role such that for those with high chronic message fatigue, even one brief exposure resulted in stronger acute message fatigue, which was associated with lower compassion and weaker willingness to help polar bears and support climate change mitigation. Discussions on these exploratory results and implications for audience segmentation are provided.